Comparison of glucose and lipid values in cord blood of newborns with small, normal and large birth weight according to gestational age (Annals of Medical Research, 2022)
Aim: Fetal growth is a complex process influenced by environmental and genetic factors. Environmental factors such as glucose, lipids and amino acids play a role in growth of the fetus. Glucose, insulin and lipid levels in the cord blood can change the birth weight according to the gestational age of the newborn. The aim of the study is to examine the relationship between glucose, insulin and lipid levels in cord blood of newborns with small (SGA), normal (AGA) and large (LGA) birth weight according to gestational age.Materials and Methods: 358 term newborns born in our hospital between January 2019 and January 2020 were included in the study. By looking at the weight percentile of the newborns, those with birth weight below the 10th percentile were considered as SGA newborns, those with birth weight of 10-90 percentiles as AGA newborns, and those with birth weight above the 90th percentile was considered as LGA newborns. Insulin, glucose, LDL cholesterol, HDL cholesterol, VLDL cholesterol, total cholesterol, and triglyceride levels of umbilical cord blood were studied after delivery.Results: Of 358 newborns included in the study, 27 (7.5%) were SGA, 312 (87.2%) were AGA, and 19 (5.3%) were LGA. The mean insulin, glucose, cholesterol and triglyceride values of the newborns in all three groups were compared. Cord blood glucose value was found lower as significantly in newborns with SGA. There was not significant difference between cord blood insulin, cholesterol and triglyceride levels of SGA, AGA and LGA newborns.Conclusion: In our study, significant correlation was found between birth weight and cord blood glucose and cholesterol levels.